Pemberdayaan Raudlatul Athfal (RA) melalui Peningkatan Kualitas SDM Guru di Daerah Nelayan Kecamatan Tugu Kota Semarang - Muslam Muslam; Fatkuroji Fatkuroji; Agus Khunaifi (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
Community service activities is carried out by using pendekataan empowerment. The essence of this approach seeks to stimulate the independence process of the community (self sustaining process) of yourself. As a result of such devotion is the First; RA teachers achieved the standard HR professionals who are able to plan and carry out learning in accordance with Permindikbud clause of 146 and 137. Second; Participants devotion has two kinds of things, namely; 1) 80% of the training participants can understand the curriculum 13, to recognize the characteristics of learners, master models and learning strategies RA 2) 85% of participants proficient in motion and song, adept at making APE in learning and being able to make RPPH in RA. Third; Teachers increasingly skilled make APE and assign tasks meaningful to students, teachers are increasingly skilled in managing the class, and implement learning strategies.